IMPROVING METHODOLOGICAL TRAINING OF FUTURE PRIMARY CLASS TEACHERS - Djumayeva Mohigul Mamanazarovna (Scholar Express Journal, 2023)
In the article, the improvement of the quality of education based on the improvement of the methodical training of the future primary school teachers, its content, forms and methods, theoretical, practical and educational importance, their inextricability in teaching students materials related to natural sciences is discussed in the article. being able to use it is one of the important factors of educational efficiency. The essence of the lessons organized on the basis of the methodical preparation of the elementary school teacher, as well as the infrastructure for its improvement, are presented.
Keywords: primary class; methodical training; future